The cerebellum : disorders and treatment - Manto, Mario; Huisman, Thierry A. G. M. (Handbook of clinical neurology, 2018)
"The Cerebellum: Disorders and Treatment, Volume 155 updates readers on the latest and clinically relevant advances in the study of cerebellar diseases in children and adults. It is organized into sections detailing: (1) Disorders (starting from the fetal cerebellum, to adult cerebellum) encountered during daily practice, and (2) Therapy (including insights into innovative drug and rehabilitative approaches). The book's innovative structure discusses cerebellar disorders in children and adults as a continuum, with its companion volume, The Cerebellum: From Embryology to Diagnostic Investigations detailing embryology, anatomy, function and diagnostic investigations and neuroimaging, including conventional sequences, diffusion tensor imaging, functional MRI, and connectivity studies"--Publisher's description